Actividad antiviral de plantas medicinales argentinas de la familia Asteraceae : identificación de compuestos bioactivos y caracterización del mecanismo de acción - Visintini Jaime, María Florencia (2015)
Finding new antiviral drugs is a necessity that is always current. One strategy for the\nidentification of new bioactive compounds is the study of the secondary metabolites that\nare present in higher plants.\nThe aim of this thesis was to study the antiviral properties on Argentinean medicinal\nplants against different viruses of clinical interest, such as poliovirus or herpes simplex\nvirus.\nA screening of the antiviral activity of two different extracts, organic extract (OE) and\naqueous extract (AE) was performed, from seven species of the Asteracecae family:\nBaccharis gaudichaudiana, B. spicata, Bidens subalternans, Eupatorium buniifolium,\nPluchea sagittalis, Tagetes minuta y Tessaria absinthioides.\nThe values of effective concentration 50 (EC50) of the OE from B. gaudichaudiana and\nE. buniifolium against PV-2 were 14.8 ± 1.5 ?g/ml and 9.5 ± 3.5 ?g/ml; respectively.\nThese values justified their further bioguided fractionation to identify the compound/s\nresponsible for the antiviral activity.\nFrom the OE of B. gaudichaudiana it was identified a known flavonoid, apigenin that\nhas been previously reported from this plant. The EC50 against PV-2 was 12.2 ± 3.3 ?M.\nThe euparin, a natural benzofuran, was identified from E. buniifolim, with a value of\nEC50 of 0.6 ± 0.2 ?M against PV-2.\nThe study of the mechanism of action of euparin demonstrated that the penetration\nand/or uncoating steps were inhibited by this compound, and the viral target was the\nhydrophobic site known as ?hydrophobic pocket? in the viral capsid; localized under the\ncanyon region. The interaction of the euparin did not affect the adsorption of the virus to\nthe cells. The selection and the biological and molecular characterization of drugresistant\nand ?dependent viral variants showed mutations associated to each phenotype,\nlocated in the different proteins of the viral capsid.\nThe results obtained in this thesis, not only identified different Argentinean medicinal\nplants as potential source of new antiviral compounds, but also identified the euparin as\na capsid inhibitor highly selective to the three human polioviruses.